BINGKAI PEMBERITAAN TINDAK DAN UPAYA BUNUH DIRI PADA REMAJA DI DETIK.COM - Razania Sani, Inatsan; Hasfi, Nurul; Nugroho, Adi (Interaksi Online, 2024)
Suicide is still considered a taboo topic for discussion, and victims or survivors of suicide often face negative stigma from society. This stigma can be formed or reinforced through media reporting, which serves as a primary source of information. Reporting on suicide attempts and actions that is not handled carefully can also trigger copycat suicide phenomena among vulnerable groups, particularly adolescents. Adolescents and young adults are the most at-risk population for suicide. Detik.com views suicide as an important issue to address, but it is crucial to pay attention to the quality and ethics of reporting, especially in relation to the sensitivity of journalists toward suicide reporting ethics.This study aims to analyze how Detik.com frames its reporting on suicide and to identify potential ethical violations in the coverage of suicide actions and attempts among adolescents. One article published during the period of January 2023 to December 2023 was selected based on three dominant narratives and analyzed using the Zhongdang Pan and Kosicki framing model. This analysis includes four elements: syntactic structure, script structure, thematic structure, and rhetorical structure. The theory used in this research is the Social Responsibility Theory and the Ethical Guidelines for Suicide Reporting.The results of the study show that there are seven frames used by Detik.com in reporting on suicide victims, namely: (1) a quiet person, (2) someone experiencing romantic issues, (3) someone who is always determined to die and lacks consideration, (4) experiencing depression or mental disorders, (5) displaying strange and puzzling behavior, (6) suicide victims by hanging, and (7) suicide victims by jumping. Ethically, the frequently violated points are points 1, 4, 9, and 14 from the Suicide Action and Attempt Reporting Guidelines from the Press Council. These violations indicate that the news is presented sensationally, spreading myths about suicide, stigmatizing the victim, and providing excessive detail about the suicide event.